Household Water Insecurity and Social Vulnerability in the Municipal Context of the Semi-Arid Region of Ceará - Tomaz, Paula Alves; Santos, Jader de Oliveira; Jepson, Wendy (Sociedade & Natureza, 2023)
Household water insecurity refers to difficulties accessing water of sufficient quality and quantity to maintain human well-being. Although this fundamental right is a premise for survival, it is not always guaranteed. This article aims to verify whether there is a correlation between household water insecurity and social vulnerability in the semi-arid region of Ceará. For this purpose, the "Household Water Insecurity Experiences – HWISE" protocol was applied to households to investigate the various problems related to water and household water supply problems. Statistical exploratory data analysis techniques were used through factor analysis, clusters, and spatial correlation to verify the spatial relationship between water insecurity and social vulnerability. The main results show that although there is a situation of household water insecurity, its connection with social vulnerability is more pronounced in urban areas. In rural areas, where vulnerability is higher, the presence of multiple water supply sources such as cisterns and water tankers conveys a higher sense of water security to the population, both in terms of access and availability of water for household consumption. Based on the achieved results, it is evident that household water insecurity requires the consideration of a wide range of factors, and its assessment cannot be accomplished solely through the use of a synthetic indicator of social vulnerability.